Sex differences in the utilization and outcomes of endovascular treatment after acute ischemic stroke: A systematic review and meta-analysis - Ouyang, Menglu; Shajahan, Sultana; Liu, Xiaoying; Sun, Lingli; Carcel, Cheryl; Harris, Katie; Anderson, Craig S.; Woodward, Mark; Wang, Xia (Frontiers in Global Women's Health, 2023)
Background: Studies of sex differences in the use and outcomes of endovascular treatment (EVT) for acute ischemic stroke report inconsistent results Methods: We systematically searched PubMed and Embase databases for studies examining sex-specific utilization of EVT for acute ischemic stroke published before 31 December 2021. Estimates were compared by study type: randomized clinical trials (RCTs) and non-RCTs (hospital-based, registry-based or administrative data). Random effects odds ratios (ORs) were generated to quantify sex differences in EVT use. To estimate sex differences in functional outcome on the modified Rankin scale after EVT, the female:male ratio of ORs and 95% confidence intervals (CIs) were obtained from ordinal or binary analysis. Results: 6,396 studies were identified through database searching, of which 594 qualified for a full review. A total of 51 studies (36 non-RCT and 15 RCTs) reporting on sex-specific utilization of EVT were included, and of those 10 estimated the sex differences of EVT on functional outcomes. EVT use was similar in women and men both in non-RCTs (OR 1.03, 95% CI 0.96-1.11) and RCTs (1.02, 95%CI 0.89-1.16), with consistent results across years of publication and regions of study, except that in Europe EVT treatment was higher in women than men (1.15, 95%CI 1.13-1.16). No sex differences were found in the functional outcome by either ordinal and binary analyses (ORs 0.95, 95%CI 0.68-1.32] and 0.90, 95%CI 0.65-1.25, respectively). Conclusions: No sex differences in EVT utilization or on functional outcomes were evident after acute ischemic stroke from large-vessel occlusion. Further research may be required to examine sex differences in long-term outcomes, social domains, and quality of life.